(untitled) (The Peerian Journal, 2022)
Tourism is a service industry. It has become a very complex activity that involves a wide range of relationships. As a result of improvements in the standard of living and disposable income with more free time, the total number of tourists is expected to increase. Factors such as convenient transportation, lack of travel restrictions, availability of information about various tourist sites and new marketing technologies contributed to the growth of the total number of tourists in the current world. In addition, a number of socio-demographic factors such as higher education standards, advances in information technology, and rapid urbanization have strongly influenced the growth of tourism. In order to prevent controversies from defining “tourism”, the World Tourism Organization has defined it as explained below: “Tourism includes the activities of persons traveling and staying in places outside their usual environment for more than one consecutive year for leisure, business and other purposes.” Tourism is different from travel. Not all travel is tourism. In order for tourism to occur, there has to be displacement. Three criteria are used simultaneously in order to describe travel as tourism